Psychological Hardiness in workers School Handicapped acoustically in laghouat - Bensayhi, Masouda (Social Empowerment Journal, 2019)
The study aimed to find out the psychological toughness level of a sample of school workers with hearing impairment in Laghouat, as well as the differences in psychological toughness according to age and social status. The results showed that there were no differences between the school staff with hearing impairment in the psychological toughness of the age and social condition.